Finite element modeling of the neuron-electrode interface. - Buitenweg, J.R (IEEE Engineering in medicine and biology magazine)
The electrical contact between an embedded microelectrode and a cultured neuron depends on the geometry of the neuron-electrode interface. The contact is improved when the electrode is covered, or sealed, completely by the neuron. In this article, the finite element method is proposed as a tool for modeling the electrical properties of the neuron-electrode interface. This method permits numerical solutions of volume conductor problems for a variety of geometries, without prior restriction of the current paths. Simulations are focused on the influence of the geometry on the transfer of an extracellularly applied stimulus current to the neuron and on the sealing resistance. A comparison is also made between finite element modeling and lumped circuit modeling. In conclusion, finite element analysis is a valuable tool for studying and optimizing the neuron-electrode contact.